1993
DOI: 10.1016/0304-3959(93)90165-l
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related barriers to management of cancer pain

Abstract: Patients' reluctance to report pain and to use analgesics are considered major barriers to pain management. To explore this problem, 270 patients with cancer completed a 27-item self-report questionnaire (BQ) that assessed the extent to which they have concerns about reporting pain and using pain medication. The 8 specific concerns included fear of addiction, beliefs that 'good' patients do not complain about pain, and concern about side effects. Patients also completed a measure of pain severity and pain inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
518
3
13

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 659 publications
(554 citation statements)
references
References 14 publications
20
518
3
13
Order By: Relevance
“…Lack of such an instrument impedes successful symptom research and improvements in routine symptom management during cancer care. 2,25 The MDASI-C, the first validated multisymptom assessment tool in China, can be applied in both clinical practice and clinical trials to evaluate the effectiveness of treatment interventions and in epidemiologic studies to estimate the prevalence of symptoms. With psychometric properties comparable to those of the MDASI-J and the original MDASI, the MDASI-C should also be widely applicable in the United States, where Chinese-speaking persons are the second largest foreign-born resident group.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of such an instrument impedes successful symptom research and improvements in routine symptom management during cancer care. 2,25 The MDASI-C, the first validated multisymptom assessment tool in China, can be applied in both clinical practice and clinical trials to evaluate the effectiveness of treatment interventions and in epidemiologic studies to estimate the prevalence of symptoms. With psychometric properties comparable to those of the MDASI-J and the original MDASI, the MDASI-C should also be widely applicable in the United States, where Chinese-speaking persons are the second largest foreign-born resident group.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to that the older and less well-educated persons were not adequately informed about their rights to receive pain relief. Ward et al (1993) found that the misconceptions and barriers to effective pain management were found to be more in the subjects with fewer years' education.…”
Section: Educational Levelmentioning
confidence: 96%
“…4,8,10 In this study, we found that subjects who are currently receiving active treatment with chemotherapy were more reluctant to communicate their pain experience to their health care professionals. Future pain interventions with cancer patients, particularly those in active treatment, should address and facilitate the communication of symptoms between patient and health care professionals.…”
Section: Discussionmentioning
confidence: 72%
“…was developed by Ward and colleagues 8 to measure patient-reported barriers to pain management. Significant (t=−2.16, P<0.05) construct validity and a factor analysis revealed four factors: 1) physiologic effects, 2) fatalism, 3) communication, and 4) harmful effects.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation